Property evolution and molecular mechanisms of aluminized colorless transparent polyimide under space ultraviolet irradiation. (May 2022) - Feng, Jiabao; Wang, Yi; Qin, Xiaogang; Lv, Yadong; Huang, Yajiang; Yang, Qi; Li, Guangxian; Kong, Miqiu
Highlights: The evolution of performance and microstructure of aluminized colorless transparent polyimide films in the simulated vacuum ultraviolet (VUV) environment are systematically investigated. The performance and microstructure for two types of aluminized colorless transparent polyimide films induced by the trifluoromethyl group and the alicyclic group are compared. The optical performance of the aluminized colorless transparent polyimide film induced by the alicyclic group has better VUV resistance. The Young's modulus, tensile strength, and the onset degradation temperature of aluminized colorless transparent polyimide films are slightly degraded after the VUV irradiation, whereas the elongation at break is significantly reduced. Both the cross-linking and breakage of the molecular structure for aluminized colorless transparent polyimide films compete during irradiation, which determines the changes of properties. Abstract: Aluminized colorless transparent polyimide (CPI/Al) film has a medium absorptivity emissivity ratio, which can keep a moderate equilibrium temperature for spacecraft, however, the property evolution and relative mechanisms under vacuum ultraviolet irradiation of CPI/Al films are rarely reported. In this work, the evolution of performance and microstructure of CPI/Al films in the simulated vacuum ultraviolet (VUV) environment is systematically investigated, in which two types of CPI films induced by the trifluoromethyl group (CPI-L/Al film) and the alicyclic group (CPI-T/Al film), respectively, are compared. It is found that the optical performance of the CPI-L/Al film is degraded more severely than that of the CPI-T/Al film, indicating better VUV resistance of the CPI-T/Al film. Specifically, for CPI-L/Al and CPI-T/Al films after 2000 ESH irradiation, the yellowness index and the solar absorptance are increased by 532.9% and 503.1%, and 157.0% and 126.7%, respectively, whereas the hemisphere emissivity is decreased by 20.8% and 6.1%, respectively. This is because the oxygen-ion escapes from the surface of CPI films and oxygen-ion vacancies are formed. Moreover, the Young's modulus, tensile strength, and the onset degradation temperature of CPI/Al films are slightly degraded after the VUV irradiation, whereas the elongation at break is significantly reduced especially for CPI-L/Al and CPI-T/Al after 2000 ESH irradiation it is decreased by 90.2% and 95.1%, respectively. This can be ascribed to the competition between the cross-linking and breakage of the molecular structure during irradiation, in which the breakage is dominant in the early stage of irradiation, leading to a great degradation in properties, and cross-linking structures are formed in the later stage of irradiation which can compensate for the degradation in properties.